Filling in the gaps: Expanding social protection in Colombia - Garda, Paula (OECD Publishing, 2022)
The pandemic has highlighted significant gaps in social protection, in particularamong informal workers. With around 60% of workers in informal jobs, many of those most in need of social protection are left behind. The government has attempted to fill this gap with non-contributory benefits, but coverage and benefit levels are low. Better-off formal workers have access to a full range of social protection benefits, involving large-scale public subsidies that widen the gap. Labour informality and social protection coverage are interlinked, as high social contributions are one of the main barriers to formal job creation. Ensuring some universal basic social protection, while simultaneously lowering the cost of formal employment, would reduce labour informality, poverty and inequality and raise productivity, all of which are long-standing challenges in Colombia
Keywords: Economics; Colombia